The distinctive national character of Japanese culture and the philosophy of Busido - Matnazarova Mukhayyo Axmetjanovna (Research Parks Publishing LLC, 2020)
This article explores the philosophy of Bushido, which is part of Japanese culture. Thoughts on Bushido philosophy, the traditional culture of the Japanese, are analyzed. There are ideas about Zen Buddhist philosophy and its essence.